دور مؤسسة الزكاة في تحويل مستحِقّي الزكاة إلى المزكّين: دراسة حالة في مؤسسة الزكاة الحكومية فرع مدينة سيمارنغ، جاوى الوسطى، إندونيسيا - Muhammad Taufiq Zam zami
This study examines one of the zakat institutions established in Indonesia, i.e., Semarang Zakat Agency. A field research has been carried out to analyze the management of Zakat in Semarang Zakat Agency, particularly in terms of the methods used in the distribution of alms to mustahiq (those who are eligible for zakat). The causes of the obstacles encountered by the institution are identified in this study and solutions to the problems are also studied. The study is based on collected data by using methods of documentation and interviews. The data is analyzed by using the inductive method and supported with deductive method to draw the conclusions from the results of zakat management implemented by the Semarang Zakat Agency. The research concludes that the funds collected by Semarang Zakat Agency are used for the benefit of eight categories of eligible recipients, and fund collection mechanism are conducted with partnership of selected banks. Zakat fund distributed to reduce the burden of dhuafa, for healthcare, and also for the educational scholarships to ease their burden. The result of this study has shown that Semarang Zakat Agency is managing their zakat fund under proper procedures. As Semarang Zakat Agency has implemented activities of accumulation, distribution, and management of zakat utility. This agency has been implementing programs to change mustahiq to become muzakki (those who pay zakat), by establishing cooperation, provision of capital and training for the jobless. The main problem faced by the Semarang Zakat Agency is the lack of awareness by Semarang society to reach a good life and lack of intention of turning themselves into muzakki. Therefore, the Semarang Zakat Agency has implemented approaches through dialogue, workshop, lecturers concerning about the information on the agency and its role in distributing zakat to the society.